Wired for dating : how understanding neurobiology and attachment style can help you find your ideal mate - Tatkin, Stan (New Harbinger Publications, Inc., 2016)
In Wired for Dating, psychologist and relationship expert Stan Tatkin offers simple. proven-effective principles drawn from neuroscience and attachment theory to help you date smart and finally find your match. You'll learn how people become attracted to one another, how to move toward or away from commitment, and the important role the brain and nervous system play in romance. The book includes exercises, real-life scenarios, and practical tips to prepare you for dating and making a meaningful connection and with a little practice, you'll be ready to meet your ideal partner.-- book cover